CULTURE RECOGNITION THROUGH SOCIOLOGY LEARNING FOR TIMOR LESTE STUDENTS - Sebastião Periera (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
This paper aims to describe the introduction of culture through sociology learning for Timor Leste students. In essence, every society has a different culture with other communities. The culture serves to regulate and meet the needs of the people living their owners. The people of Timor Leste have different cultures from other communities. This difference is due to differences in the environment and subsystems of communities in Timor-Leste. Every member of the community needs to understand and live the culture in order to overcome the problems faced in life. In the world of education, cultural understanding can be obtained through learning Sociology. Therefore, sociology subject matter that is filled with community culture can provide significant benefits to the students.